Environmental Uncertainty And Firm Performance: The Moderating Role Of Corporate Governance - Reyry Aprisma; Erina Sudaryati (Jurnal Akuntansi, 2020)
This research aimed to examine the effect of environmental uncertainty on firm performance. This research added corporate governance as a moderating variable. The research samples were manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2018 which were selected using purposive sampling techniques. The samples analyzed were 442 company data. The result showed that environmental uncertainty has a negative effect on firm performance. The result indicated environmental uncertainty causes operating expenses to increase so that the firm performance decreases. In addition, the results showed that corporate governance reduced the effect of environmental uncertainty on firm performance. The result indicated corporate governance is able to reduce the impact of environmental uncertainty so that firm performance increases.